Reclaimed Water and Florida's Water Reuse Program - Christopher J. Martinez; Mark W. Clark (EDIS, 2009)
AE448, a 5-page illustrated fact sheet by Christopher J. Martinez and Mark W. Clark, describes Florida’s program for reusing water from municipal wastewater treatment plants that has been treated to allow for safe use for designated purposes — why reuse this water, how it is used in Florida, how it is produced, and treatment requirements. Includes references. Published by the UF Department of Agricultural and Biological Engineering, July 2009.